Analysis of Syntaxic Errors in Indonesian Writing: A Literature Review - Agustina, Ria; Ramadhan , Syahrul; Mukhaiyar, Mukhaiyar (Indonesian Research Journal in Education |IRJE|, 2023)
This article summarizes various research results regarding syntactic language errors in Indonesian. Data were collected from 27 diverse research articles. The research methods used tend to be qualitative. The research results reveal various syntactic errors found in Indonesian writing. Common errors include errors in sentence structure, word choice/diction, spelling, word accuracy, sentence clarity, and sentence logic. Linguistic factors such as regional language influences, inappropriate loan words, and certain particles also influence syntactic errors. Lack of practice-based learning was also found to be a factor influencing the occurrence of syntactic errors. This research indicates that syntactic errors are a widespread problem in Indonesian, and improvement and learning of Indonesian needs to cover various text types and communication contexts. These findings provide valuable insights for improving the quality of communication in Indonesian and underline the need for a more practical and contextual learning approach to overcoming the problem of syntactic language errors.